Hypoxic Preconditioning Enhances Cellular Viability and Pro-angiogenic Paracrine Activity: The Roles of VEGF-A and SDF-1a in Rat Adipose Stem Cells - Zhao, Yang; Zhang, Ming; Lu, Guo-liang; Huang, Bao-xing; Wang, Da-wei; Shao, Yuan; Lu, Mu-jun (Frontiers in Cell and Developmental Biology, 2020)
To achieve the full therapeutic potential of implanted adipose-derived stem cells (ASCs) in vivo, it is crucial to improve the viability and pro-angiogenic properties of the stem cells. Here, we first simulated the conditions of ischemia and hypoxia using the in vitro oxygen-glucose deprivation (OGD) model and confirmed that hypoxia preconditioning of ASCs could provide improved protection against OGD and enhance ASC viability. Second, we assessed the effect of hypoxia preconditioning on pro-angiogenic potential of ASCs, with a particular focus on the role of vascular endothelial growth factor-A (VEGF-A) and stromal derived factor-1a (SDF-1a) paracrine activity in mediating angiogenesis. We found that the conditioned medium of ASCs (ASCCM) with hypoxia preconditioning enhanced angiogenesis by a series of angiogenesis assay models in vivo and in vitro through the upregulation of and a synergistic effect between VEGF-A and SDF-1a. Finally, to investigate the possible downstream mechanisms of VEGF/VEGFR2 and SDF-1a/CXCR4 axes-driven angiogenesis, we evaluated relevant protein kinases involved the signal transduction pathway of angiogenesis and showed that VEGF/VEGFR2 and SDF-1a/CXCR4 axes may synergistically promote angiogenesis by activating Akt. Collectively, our findings demonstrate that hypoxia preconditioning may constitute a promising strategy to enhance cellular viability and angiogenesis of transplanted ASCs, therein improving the success rate of stem cell-based therapies in tissue engineering.